Host genotype affects endotoxin release in excreta of broilers at slaughter age - Marcato, F.; Rebel, J. M. J.; Kar, S. K.; Wouters, I. M.; Schokker, D.; Bossers, A.; Harders, F.; van Riel, J. W.; Wolthuis-Fillerup, M.; de Jong, I. C. (Frontiers in Genetics, 2023)
Host genotype, early post-hatch feeding and pre- and probiotics are factors known to modulate the gut microbiome. However, there is a knowledge gap on the effect of both chicken genotype and these dietary strategies and their interplay on fecal microbiome composition and diversity, which in turn can affect the release of endotoxins in the excreta of broilers. Endotoxins are a major concern as these can be harmful for both animal and human health. The main goal of the current study was to investigate whether or not it was possible to modulate the fecal microbiome and thereby reducing endotoxin concentrations in the excreta of broiler chickens. An experiment was carried out with a 2 × 2 × 2 factorial arrangement including 3 factors: 1) genetic strain (fast-growing Ross 308 vs. slower-growing Hubbard JA757); 2) no vs. combined use of probiotics and prebiotics in the diet and drinking water; 3) early feeding at the hatchery vs. non early feeding. A total of 624 Ross 308 and 624 Hubbard JA757 day-old male broiler chickens were included until d 37 and d 51 of age, respectively. Broilers (N=26 chicks/pen) were housed in a total of 48 pens, and there were 6 replicate pens/treatment group. Pooled cloacal swabs (N=10 chickens/pen) for microbiome and endotoxin analyses were collected at a target body weight (TBW) of 200 g, 1 kg and 2.5 kg. Endotoxin concentration significantly increased with age (P= 0.01). At TBW of 2.5 kg, Ross 308 chickens produced a considerably higher amount of endotoxins (Δ=552.5 EU/ml) than Hubbard JA757 chickens (P < 0.01). A significant difference in the Shannon index was observed for the interaction between use of prebiotics and probiotics and host genotype (P=0.02), where Ross 308 chickens with pre-/probiotics had a lower diversity compared to Hubbard JA757 chickens with pre-/probiotics. Early feeding did not affect both fecal microbiome and endotoxin release. Overall, the results suggest that chicken genetic strain may be an important factor to take into account regarding fecal endotoxin release, although this needs to be further investigated under commercial conditions.